Potential Avoidability: A Statistic for Controlling In-Patient Utilization in Acute Care Hospitals - Chorba, R. W. (Management Science, 1976)
A patient-day of service is classified as potentially avoidable if the unique facilities and manpower of an acute care hospital are not essential to providing the services received. From a practical standpoint, not all potentially avoidable days are truly avoidable. However, norms can be established, specific to diagnosis, surgery, sex, and age, which specify an acceptable range for the percentage of potentially avoidable days. A procedure is developed for efficiently assessing potential avoidability, making it feasible to measure this concept for every patient on a daily basis. The resultant data base can then be used in utilization review screening to detect abnormal patterns of utilization by case, physician, or hospital.